Massive Gastrointestinal Bleeding from a Jejunal Dieulafoy Lesion: An Extraordinary Presentation - Majdi Saada; Shay Perek; Mohammad Agbaria; Ayelet Raz-Pasteur (Case Reports in Gastroenterology, 2019)
We present an atypical and rare case of a previously healthy 27-year-old male who presented with acute onset of abdominal pain, bloody diarrhea, and syncope. At the Emergency Department, vital signs were stable with no signs of shock. Physical examination revealed diffuse tenderness of the abdomen and cherry red blood was noted upon rectal examination. Blood tests showed marked leukocytosis without anemia. Sigmoidoscopy was performed which revealed hematochezia with no obvious site of bleeding. The patient was admitted to the hospital with a working diagnosis of dysentery and received supportive care. During the following days, blood tests revealed an ongoing decline of hemoglobin levels which necessitated a new workup of gastrointestinal bleeding. Investigation modalities including upper and lower endoscopies as well as angiography failed to demonstrate a bleeding site. Scintigraphy, which was performed next, demonstrated an increased radiotracer activity in the right abdomen consistent with small bowel bleeding. Following these results, the patient underwent urgent laparotomy and surgical resection was performed. The histopathological findings were consistent with a Dieulafoy lesion. This case illustrates the importance of the complementary role of various modalities in locating the bleeding site along the gastrointestinal tract.